A Randomized Double Blind Study On Antiemetic Effect Of Ondansetron And Glycopyrolate During Cesarean Section (Journal of Pharmaceutical Negative Results, 2023)
In this randomized double blind study anti-emetic effect of ondansetron and glycopyrrolate was evaluated in parturients during cesarean section. Inspite of number of antiemetics available, their effectiveness and fetal safety profile when used in parturients remains debatable. This comparative study of randomized double-blind was designed with an aim to compare the antiemetic effects of Ondansetron and glycopyrrolate during cesarean section. Twenty-four parturients scheduled for elective cesarean section was randomized to receive intravenous ondansetron 4 mg (Group O, n=24) or glycopyrrolate 0.2 mg (Group G, n=23) before spinal anesthesia. Data on postoperative episodes of hypotension, bradycardia and pain was measured till 10 h. The data was analyzed by using statistical analysis method. Statistically there was no significant difference between nausea and vomiting at all the study intervals between the two groups. There was no difference in patients of hypotension, but patients of bradycardia were significantly less in glycopyrrolate group than in ondansetron group, glycopyrrolate shows the incidence of dry mouth with more significant as compared to ondansetron group. The effect of glycopyrrolate in nausea and vomiting patients during cesarean section are comparable to ondansetron, but with an increased incidence of dry mouth. Glycopyrrolate has no effect on hypotension, but the incidence of bradycardia is significantly less.